STUDI PERUBAHAN PENGGUNAAN LAHAN DI DAS BADUNG - A.R. As-syakur; I.W. Suarna; I.W. Sandi Adnyana; I.W. Rusna; I.A. Alit Laksmiwati; I.W. Diara (Environmental Research Center (PPLH) of Udayana University, 2010)
Land use change in a watershed could affect the ecological system, hydrological system and water quality, meanwhile land use change study is needed to conduct especially in Badung watershed. The purpose of this research is to calculate land use changes from 1992 to 2008 and predicted hectarege of land use in 2015 and 2020. Methods of this research are comparing the four land use maps obtained from Bakosurtanal (1992 and 2000), Interpretation of Landsat ETM+ image (2003), and interpretation of ALOS/AVNIR-2 image (2008). On-screen method is used to ALOS/AVNIR-2 image data interpretation. The equation obtained from logarithmic regression is used to predict the land use area. The results of this research showed that the land use in Badung Watershed region has changes from 1992 to 2008. Settlement land use has the largest changes, where the area is increase. The speed of land use change of settlement reached 46,45 ha per year, while the ricefield land use reached 38,91 ha per year. Predicted settlement area in 2015 and 2020 is 2056,83 ha and 2108,83 ha, while the ricefield is 1386,79 ha and 1343,66 ha.